The social entrepreneur puzzle: the background, personality and motivation of Israeli social entrepreneurs. Issue 2 (4th May 2019) - Cohen, Hilla; Kaspi-Baruch, Oshrit; Katz, Hagai
Abstract: This study compares the personality, motivation and leadership background of 104 Israeli social entrepreneurs and 85 business entrepreneurs. Social entrepreneurs are higher in extraversion and openness to experience, lower in managerial personality characteristics, and more driven by ideology rather than by capital gains. Social entrepreneurs also have stronger early ideological and leadership training. Multiple regression analysis reveals that a relatively robust and persistent set of internal psychological drivers prompt a search for specific experiences that are related to leadership roles and social change orientations, including social entrepreneurship and the relevant leading experiences in adolescence and young adulthood.